(untitled) - OLIVEIRA, Thamyres Lima (2022)
Analysis about of methods of conservation and preservation of paper documents carried out in the Public Archive of the State of Pará - (APEP), identifying potentialities and possible weaknesses. To carry from work, was used, as methodology, bibliographic research, where material was raised referring conservation and preservation of documents, and about the history, characteristics and agents of paper deterioration. The data analysis was of character exploratory and case study, with the object of research focused on the Public Archive of the State of Pará, from site visit and application from the interview script with director of the archive. From the results obtained, it was identified that the Public Archive of the State of Pará performs successfully the practices of preservation and conservation of documents but being suggested greater financial support to enhance these initiatives in the institution.